2018
DOI: 10.1504/ijogct.2018.10006334
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Croatian superhigh-organic-sulphur Raa coal, imported low-S coal, and bottom ash: their Se and trace metal fingerprints in seawater, clover, foliage, and mushroom specimens

Abstract: The Labin City area has represented the major Croatian coal mining, metal industry and coal-fired electricity centre for more than two centuries. The domestic superhigh-organic-sulphur (SHOS) Raša coal is a unique variety compared to other coal types worldwide, based on its highest organic sulphur values, up to 11%. It was utilised in the Plomin coal-fired power plant during the period 1970-2000, and was replaced by an imported lowS coal afterwards. This paper presents the levels of S, Se, V, U, Hg, Sr, Cd, Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Vanadium was found elevated in stream samples, while its levels in seawater were only slightly below world values. These ndings are in accordance with Kendall's tau correlation coef cients (>0.99, p < 0.05) calculated for all the pairs of S, Se, V and U in SHOS Raša coal samples, reported by Meduni et al (2017). Uranium is a non-essential, chemotoxic, radiotoxic, and carcinogenic element, while V is an essential nutrient for many animals, but it can be toxic depending on its speciation and oxidation state (Reimann & de Caritat, 1998).…”
Section: Element Levels In Water Samplessupporting
confidence: 90%
See 1 more Smart Citation
“…Vanadium was found elevated in stream samples, while its levels in seawater were only slightly below world values. These ndings are in accordance with Kendall's tau correlation coef cients (>0.99, p < 0.05) calculated for all the pairs of S, Se, V and U in SHOS Raša coal samples, reported by Meduni et al (2017). Uranium is a non-essential, chemotoxic, radiotoxic, and carcinogenic element, while V is an essential nutrient for many animals, but it can be toxic depending on its speciation and oxidation state (Reimann & de Caritat, 1998).…”
Section: Element Levels In Water Samplessupporting
confidence: 90%
“…SHOS Raša coal seams were mined at nearby localities, from the second half of the 18th century until the late 1990s (Meduni et al, 2016a). A medical study (Mohorovi , 2003) established the correlation between ground SO 2 levels and health problems of pregnant women and small children due to exceptionally high S values in superhigh-organic-sulphur (SHOS) Raša coal (Meduni et al, 2017). Meduni et al (2016b) determined that soil around a coalred power plant (PPP), which used SHOS coal during the period between 1970 and 2000, is severely polluted with S, polycyclic aromatic hydrocarbons (PAHs), Se, and Cd, while ues are markedly increased in SHOS Raša coal compared to coal Clarke values (Yudovich & Ketris, 2006), Meduni et al (2017) found slightly increased Se in aquatic (seawater of the Plomin Bay) and herbal (clover and foliage) samples.…”
Section: Introductionmentioning
confidence: 99%